Weekly Formative Exams and Creative Grading Enhance Student Learning in an Introductory Biology Course - Bailey, E. G. (CBE Life Sci Educ, 2017)
First-year students often become discouraged during introductory biology courses when repeated attempts to understand concepts nevertheless result in poor test scores. This challenge is exacerbated by traditional course structures that impose premature judgments on students’ achievements. Repeated testing has been shown to benefit student ability to recognize and recall information, but an effective means to similarly facilitate skill with higher-order problems in introductory courses is needed. Here, we show that an innovative format that uses a creative grading scheme together with weekly formative midterm exams produced significant gains in student success with difficult items requiring analysis and interpretation. This format is designed to promote tenacity and avoid discouragement by providing multiple opportunities to attempt demanding problems on exams, detailed immediate feedback, and strong incentives to retain hope and improve. Analysis of individual performance trajectories with heat maps reveals the diversity of learning patterns and provides rational means for advising students.